Contemporary Da'wah Transformation :: Study on Commodification of Virtual Da'wah through YouTube - Nisa, Nanda Fahrun (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2024)
This research discusses the transformation of contemporary da'wah through digital platforms, especially YouTube, as a virtual da'wah medium. In the digital era, da'wah is no longer limited to physical space, but has developed through online media, which allows religious messages to reach a wider and more diverse audience. One of the important phenomena that has emerged is the commodification of da'wah, where religious content not only serves as a means of spreading Islamic values, but also as a commercial product that can be monetized. This study explores how da'wah through YouTube undergoes commodification, identifies the forms of commodification that occur, and its impact on the authenticity of the da'wah message itself. Through a qualitative approach with content analysis on a number of popular da'wah channels on YouTube, this study reveals that the commodification of da'wah not only has an impact on the way messages are conveyed, but also on delivery strategies that are tailored to meet the demands of the digital market. The results of this study show that there is an ambiguity between the purpose of da'wah as the dissemination of religious values and as an economic activity influenced by algorithms and social media trends.